Human Platelet Storage Organelles A Review - Fukami, Miriam H.; Salganicoff, Leon (Thrombosis and Haemostasis, 1977)
Platelets contain numerous electron-dense subcellular organelles which have been referred to in the literature by various names such as α-granules, electron-dense and very electrondense granules, lysosomes, dense bodies, etc. Most of the organelles are secretory granules, since induction of secretion by appropriate stimuli causes degranulation of platelets and the appearance of the granule contents in the extracellular medium. Among the substances that are known to be stored and secreted by platelets are: serotonin, ATP, ADP, calcium, pyrophosphate, acid hydrolases, fibrinogen, vascular permeability factor, β-thromboglobulin, platelet factor 4 and growth factor.The recent literature concerning the localization of the secreted substances within specific platelet organelles is reviewed here. Results from electron microscopy and microprobe analysis, selective secretion experiments, subcellular fractionation studies and studies on platelets from patients with storage pool deficiency indicate that there are as many as four types of storage organelles in human platelets.